Microbioma ruminal ativo de Nelore: efeitos da dieta e interações com emissão de metano, eficiência alimentar - Silva, Juliana Virginio da (Universidade Federal de São Carlos, 2025)
The growing global demand for beef, particularly from production systems in tropical regions, requires innovative strategies that enhance feed efficiency and reduce the environmental impacts of livestock. The ruminal microbiome plays a central role in the digestion of complex carbohydrates and the production of volatile fatty acids, which are the primary energy source for ruminants. In Brazil, the Nelore breed (Bos indicus) and its crossbreeds represent approximately 80% of the national herd. However, functional studies on the ruminal microbiome of this breed are still scarce. Advances in omics technologies now allow the investigation of how diet, the microbiome, and the host genome affect productive and environmental efficiency in beef cattle. Therefore, this study aimed to investigate the activity of the ruminal microbiome in a population of 52 Nelore cattle subjected to two distinct diets (conventional and byproducts) and to integrate, in an unprecedented manner, metagenomic, metatranscriptomic, and rumen wall microRNA data. To achieve this, we set the following objectives: Characterize the active functional profile of the ruminal microbiome in response to different diets using metatranscriptomic data; Assess the taxonomic and functional composition of the active ruminal microbiome by integrating metagenomic and metatranscriptomic data; Associate the active microbiome with methane emissions and feed efficiency; Investigate the interaction between the active microbiome and the host genome by integrating rumen wall microRNA expression with functional and taxonomic information of the microbiome. Metatranscriptomic analyses revealed key functional shifts in the rumen microbiome, despite relatively stable taxonomic composition across diets. Dietary components directly influenced microbial metabolism. In the conventional diet group, most expressed functions were associated with the metabolism of readily fermentable carbohydrates such as starch and mannose, present in corn and soybean meal. In contrast, animals receiving the by-product diet exhibited microbial activities linked to the degradation of complex carbohydrates, such as the cellulose found in citrus pulp. Additionally, the inclusion of by-products favored alternative microbial pathways that compete with methanogenesis, such as the reductive acetogenesis pathway (e.g., tetrahydrofolate synthase), which can redirect H₂ and CO₂ toward acetate production. Increased expression of folylpolyglutamate synthase/dihydropteroate synthase was also observed, potentially indicating methionine limitation and reducing the availability of essential substrates for methanogenesis, such as methanofuran and methanopterin. To further deepen our understanding of the rumen microbiome, we constructed a rumen prokaryotic gene catalog that revealed taxonomic and functional differences between the total metagenome (Nelore Ruminal Prokaryotic Microbiome Genes – NRPMG) and its transcriptionally active fraction (active-Nelore Ruminal Prokaryotic Microbiome Genes – aNRPMG). These findings indicate that fermentative processes in the rumen are shaped primarily by the functional activity of microbial communities, rather than their mere presence. We also identified enzymes and taxa associated with methane emissions and feed efficiency. Among them, Carbohydrate Esterase family 20 (CE20), Glycoside Hydrolase family 15 (GH15), and the genera Monoglobus and Halosimplex emerged as potential indicators or modulators of host performance traits. Finally, the analysis of host–microbiome interactions revealed co-expression patterns among rumen wall microRNAs, enzymes, and active microbial genera, suggesting meaningful host–microbiome interplay. These microRNAs may modulate the gene expression of enzymes or microorganisms involved in specific metabolic functions, including lipid metabolism and host health processes. Overall, the findings of this thesis reinforce that the rumen microbiome should be understood not only through its composition but, more importantly, through its functional activity. The integrative approach adopted here highlights how the interplay among microbiome, host, and diet shapes key metabolic processes and underscores microbial and molecular targets with potential to support strategies aimed at mitigating methane emissions and improving feed efficiency in cattle raised in tropical environments.
Active rumen microbiome of Nellore cattle: effects of diet and interactions with methane emissions and feed efficiency
Keywords: Atividade da microbiota; Bos indicus; Holobionte; Metatranscriptoma; Metagenoma; microRNA; CIENCIAS BIOLOGICAS::GENETICA::GENETICA MOLECULAR E DE MICROORGANISMOS; 2. Fome Zero e Agricultura Sustentável